Analysis of the Importance of Human Resource Competence in Improving Employee Performance in Zulpah Batik Madura MSMEs - Ulfa Afriant; Mochammad Isa Anshori (SAJMR : Southeast Asian Journal of Management and Research, 2024)
MSMEs are able to support our country's economy, because most business actors are MSMEs and are able to absorb labor. This study aims to determine the role of MSME HR competencies in improving the performance of MSMEs Zulpah Batik Madura. This research uses a type of qualitative research, which is research that is used to research the condition of natural objects where the researcher is a key instrument. Human resource competence (HR) turns out to be one of the most important factors in the MSME industry. With the increase in human resource competence through increasing knowledge and skills, this is the key to improving the performance of MSMEs. Human resource management in MSMEs also includes recruitment, selection, placement, development, compensation (wages), retention, evaluation, promotion to termination of employment relationships. Managing human resources for MSMEs is a skill that must be possessed by MSME actors